PEMANFAATAN TEKNOLOGI ARDUINO DAN DFPLAYER MINI UNTUK PERANGKAT PEMUTAR AUDIO DI MASJID RAUDHATUL JANNAH DESA GONTAR, KABUPATEN SUMBAWA, NUSA TENGGARA BARAT - Paris Ali Topan; Dinda Fardila; Sopyan Ali Rohman; Syamsul Bahri; Jenal Jenal; Yogi Febriansyah (Jurnal Abdi Insani, 2022)
Religious activities in mosques are always marked by playing MP3 audio, for example just before the call to prayer is sounded, generally mosques in Sumbawa will play several MP3 files first and then the call to prayer is echoed. Changing MP3 audio from one playback session to another is done by replacing the flash drive that has been filled with certain MP3 files. This condition is less efficient for the management of the Raudhatul Jannah mosque in Gontar Village, Sumbawa. So from these conditions an idea occurred to make a compact audio player device so that every MP3 change that will be played does not need to replace the flash drive. This audio player system is made using Arduino technology which is connected to an MP3 player device, namely DFPlayer mini. There are several steps involved in making this device, namely: designing the PCB as a place for the supporting electronic devices to be arranged, programming the Arduino so that it can communicate with the mini DFPlayer device, and finally compiling the supporting components such as the keypad and power unit and conducting a test. This device has been successfully made and has been installed in the Raudhatul Jannah mosque, a brief description of this device, namely: it has a keypad that is useful for selecting MP3 files to be played, has an audio jack on the bottom to communicate with the main audio device.